Bariatric surgery is associated with a lower rate of death after myocardial infarction and stroke: A nationwide study. Issue 9 (17th June 2019) - Aminian, Ali; Aleassa, Essa M.; Bhatt, Deepak L.; Tu, Chao; Khorgami, Zhamak; Schauer, Philip R.; Brethauer, Stacy A.; Daigle, Christopher R.
Abstract: Aim: To assess the potential protective effect of bariatric surgery on mortality after myocardial infarction (MI) or cerebrovascular accident (CVA). Materials and Methods: Using the National Inpatient Sample (2007‐2014), 2218 patients with a principal discharge diagnosis of acute MI and 2168 patients with ischaemic CVA who also had history of prior bariatric surgery were identified. Utilizing propensity scores, these patients were matched 1:5 with patients who had similar principal diagnoses but no history of bariatric surgery (controls). Control group‐1 included participants with obesity (BMI ≥ 35 kg/m 2 ) only and participants in control group‐2 were matched according to post‐surgery BMI with the bariatric surgery group. The primary and secondary endpoints were in‐hospital all‐cause mortality and length of hospital stay, respectively. Outcomes after MI and CVA were separately compared among groups in multivariate regression models. Results: A total of 48 300 (weighted) participants were included in the analysis. The distribution of covariates was well balanced after propensity matching. Mortality rates after MI were significantly lower in patients with a history of bariatric surgery compared with control group‐1 (1.85% vs 3.03%; odds ratio (OR), 0.61; 95% confidence interval (CI), 0.44‐0.86; P = 0.004) and with control group‐2 (2.00% vs 3.26%; OR, 0.62; 95% CI, 0.44‐0.88; P = 0.008). Similarly, in‐hospital mortality rates after CVA were significantly lower in patients with a history of bariatric surgery compared with control group‐1 (1.43% vs 2.74%; OR, 0.54; 95% CI, 0.37‐0.79; P = 0.001) and with control group‐2 (1.54% vs 2.59%; OR, 0.61; 95% CI, 0.41‐0.91; P = 0.015). Furthermore, length of stay was significantly shorter in the bariatric surgery group for all comparisons ( P  < 0.001). Conclusion: Prior bariatric surgery is associated with significant protective effect on survival after MI and CVA.